The Impact of Corporate Leverage on Innovation Performance: Empirical Evidence from China - Lin,Chaobiao; Zhang,Heng (2025)
Against the backdrop of the accelerated advancement of a new round of technological revolution and industrial transformation, the global economy is moving towards a development model driven by innovation as its core. Enterprises, as important carriers of technological progress and institutional innovation, are facing increasingly fierce market competition and transformational pressures. In this process, continuous technological innovation stands as a critical pathway for enhancing enterprises' core competitiveness and sustaining their development. However, innovation activities are generally characterized by long cycles, high risks, and substantial investments, leading enterprises to face significant financing constraints. Given the limitations of internal funds, such as restricted access and insufficient quantities, which often fail to effectively cover the high-intensity investment demands of innovation activities, enterprises are increasingly relying on external financing tools to alleviate financial pressures. Among various external financing methods, debt financing is widely utilized in corporate innovation practices due to its advantages of rapid financing speed and relatively lower information disclosure requirements, becoming an important source of funds to support R&D activities. However, debt financing is accompanied by financial leverage effects, debt repayment pressures, and moral hazards, potentially exerting a double-edged sword effect on corporate innovation. Therefore, exploring the impact mechanisms and differential effects of different types of debt financing on corporate innovation holds significant theoretical value and practical implications for clarifying the relationship between capital structure and innovation, as well as optimizing financing decisions. Based on traditional capital structure theories, this paper employs dynamic panel data from 2,063 non-financial A-share listed companies in China from 2007 to 2024 as a sample. It constructs an innovation performance evaluation system from three dimensions: innovation input, innovation output, and innovation efficiency, to study the impact of corporate leverage on innovation performance. Through empirical analysis using a two-way fixed effects model, it is found that there exists a significant inverted U-shaped relationship between corporate leverage ratio and innovation performance. The underlying mechanism manifests as follows: moderate debt activates R&D resources by alleviating financing constraints, while excessive debt triggers dual suppression. Financial pressures compel R&D budget cuts (with innovation output elasticity turning negative when the debt ratio exceeds 40%), and agency problems arising from creditor supervision lead management to avoid high-risk explorations. Through calculations, the inflection points for innovation input, output, and efficiency are identified as 38.05%, 40.30%, and 39.55%, respectively, forming an optimal leverage range of 38%-40%. Heterogeneity analysis based on debt types reveals that both short-term and long-term debts have significant impacts on innovation output, with short-term debts exhibiting higher inflection point values. In terms of debt sources, corporate credit leverage ratios demonstrate a more significant positive impact on innovation output performance. Further discussions on endogeneity issues and robustness tests by replacing relevant variables yield consistent results, ensuring the reliability of this paper's research conclusions. Finally, based on the empirical results, relevant suggestions for optimizing financial leverage are proposed from both macro policy-making and micro enterprise perspectives to promote corporate innovation and development.
Keywords: Corporate Leverage; Innovation Performance; Fixed Effects Model; Innovation Efficiency; Nonlinear Relationship